The Allylic Acetoxylation of 1,1-Disubstituted Alkenes Catalyzed by a Palladium(II)/Monothiadiazole Ligand System - Li, Xiaohan; Sun, Bin; Yang, Jin; Zhang, Xun; Wang, Jiayang; Zhuang, Xiaohui; Jin, Can; Yu, Chuangming (Synlett, 2019)
A palladium(II)/monothiadiazole ligand catalytic system and its application in catalyzing the acetoxylation of 1,1-disubstituted alkenes have been developed. With this newly designed monothiadiazole thioether ligand, the reaction showed a broad scope with respect to 1,1-disubstituted olefins, giving the corresponding products in yields of 30–86%.
Keywords: palladium catalysis; ligands; acetoxylation; alkenes; regioselectivity; allylic oxidation